WEBJORNALISMO COLABORATIVO - A PRESENÇA DOS USUÁRIOS NO CONTEÚDO INFORMATIVO DO PORTAL R7 - VIEGAS, ROBERTA POLIANI (2015)
The objective of this study is check how works the internet users collaboration in the informative content of “Portal R7” since the web 2.0 was creation in 2004. The term web 2.0 appeared to qualify a second generation of services and communities, in a new interaction and participation environment that includes several languages. With the growth of digital technology accession, some barriers that limited the collaboration in informative contents were overcome and the communication environment becomes an experience exchange local and daily practices.In this scenario, the surfers now have a near relationship in the media processes present in the digital support, in which citizens can express, be more visible and relate from the moment that his produce, post and share any type of content, could be informative or entertainment.The literature review covers the authors such as Ciro Marcondes Filho, José Marques de Melo, Nelson Traquina, Alex Primo, Ana Brambilla, Marcelo Träsel, Raquel Recuero, Polyana Ferrari, Squirra, among others.The research method used is qualitative, through a descriptive exploratory research, like a case study.The instruments for research were the direct observation and the semi-structured interview (or semi-open). The main result is that the collaborate web journalism in the “Portal R7” it is primarily induced by social networks, in specially Facebook and Twitter inspired by call for action like a strategy to call the collaboration.The journalist practices are intrinsically dependent on user’s actions, and the journalist adds to the check practices a new stage related a relationship with the Portal user to assemble and retain the audience, enhancing the cooperation in all production stages